Experimental study on low-velocity impact responses and residual properties of composite sandwiches with metallic foam core. (1st September 2019) - Huo, Xintao; Sun, Guangyong; Zhang, Haiyang; Lv, Xiaojiang; Li, Qing
Abstract: Performances of lightweight sandwich panels can be enhanced by proper combination of facesheets and core. To promote sandwich structures for automobile applications, this study aimed to investigate the crashworthiness and residual performance of metallic foam based sandwich panels. Three types of facesheet materials (i.e. aluminum alloy Al6061, glass fiber reinforced plastic (GFRP) and carbon fiber reinforced plastic (CFRP)) with different Young's moduli and ultimate strengths were considered; and the effects of skin thickness, core density and core height were evaluated under both low-velocity off-panel pre-impact and in-panel post-compression. The compression after impact (CAI) tests were conducted in a full range of impact energy up to structural penetration of sandwich panel. The loading process and failure mechanism were scrutinized based upon the internal damage and external deformation modes, acquired by computerized tomography (CT) scan as well as in-situ 3D digital image correlation (DIC) techniques, respectively. Under the low-velocity pre-impact, two typical load-displacement responses, namely double-peak and triple-peak patterns, were observed. It was found that impact resistance of the sandwiches with Al6061 facesheets was higher than that with fiber reinforced plastic (FRP) laminated facesheets, meaning that ductile materials could be a better choice for sandwich facesheets when the impact resistance is a primary concern. For the in-panel post-compression test, it was found that the Al6061 facesheet failed in a collapse mode due to buckling; while the FRP laminated facesheet damaged in a form of fracture. Besides, the experimental results revealed that the specimens with Al6061 facesheets exhibited advantages in terms of peak load, energy absorption and the specific energy absorption ( SEA ). Nevertheless, the sandwiches with the FRP laminated facesheets demonstrated better structural integrity and residual performance of mechanical responses after the pre-impact.